Book Review: “Constitutional Confrontation in Hong Kong” & “The Future of the Law in Hong Kong” - Davis Macmillan, Michael C.; Wacks, Raymond (Columbia Journal of Asian Law, 1990)
The shape of Hong Kong’s legal future is slowly coming into view following ratification in March, 1989 of the Basic Law of the Hong Kong Special Administrative Region of the Peoples Republic of China (hereinafter Basic Law) by the National People’s Congress. Two recent books map out areas of conflict projected for the post- 1997 period, when China and Hong Kong become in the words of Deng Xiaoping “one country, two systems.”1 Both books, written in the more hopeful climate just prior to June 1989, suggest important areas for legal reform in the transition period.